Peningkatan Kapasitas Aparatur Desa Pameuntasan dalam Pemanfaatan Tanda Tangan Digital untuk Mendukung Transformasi Digital Pemerintahan Desa - Arifin, Rifqi Khairul; Ariesmansyah, Andre (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The world is currently transitioning to an information society. Indonesia must adapt to these changes to avoid being left behind by global progress if it fails to transform and respond to developments in information technology. Because information technology is developing rapidly, information, data, and knowledge can be created very quickly and disseminated worldwide and across all levels of society within seconds. This means that anyone can communicate directly with anyone else on the planet without the need for intermediaries or mediation. The focus of the Pameuntasan Village Apparatus Capacity Building Program in the Use of Digital Signatures is to improve employee skills in utilizing digital signature technology in public service administration processes. The challenges faced by partners include: not all employees have basic knowledge of digital technology, which makes it difficult for them to use digital signatures effectively; lack of software or systems that can effectively integrate digital signatures, which hinders administrative processes; and a lack of understanding of how digital signatures function to maintain data security and how to prevent potential misuse, which can hinder their implementation. As a result of the PKM (Community Service Program), it is expected that Pameuntasan Village Apparatus will have a better understanding of digital signature technology and be able to use it confidently in carrying out administrative tasks. This includes understanding how to digitally sign documents and integrating them into the village administration system. The use of digital signatures will accelerate administrative processes in the village, reduce reliance on physical documents, and expedite the approval of letters, permits, and other important documents.